2022
DOI: 10.1124/dmd.122.000934
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccines and the Virus: Impact on Drug Metabolism and Pharmacokinetics

Abstract: List of non-standard abbreviations: alanine serine cysteine transporter (ASCT), antibody-drug conjugates (ADCs), excitatory amino acid transporter (EAAT), gamma aminobutyric acid (GABA), glycine transporter (GLYT), interferon (IFN), interleukin (IL), mean fluorescence intensity (MFI), nuclear factor kappa B (NF-κB), post-acute covid-19 syndrome (PACS), pegylated (PEG), polyinosinic:polycytidylic acid (Poly(I:C)), small neutral amino acid transporter (SNAT)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 130 publications
0
9
0
Order By: Relevance
“…This interaction is extended to drug transporters and other organs which finally exert impact on drug absorption, distribution, metabolism and excretion (ADME), the primary pharmacokinetic clearance pathways for complex formulations (e.g. nanoparticles, biologics) [ 143 ]. For instance, altered ADME of drugs have been observed in Covid-19 infection and vaccination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This interaction is extended to drug transporters and other organs which finally exert impact on drug absorption, distribution, metabolism and excretion (ADME), the primary pharmacokinetic clearance pathways for complex formulations (e.g. nanoparticles, biologics) [ 143 ]. For instance, altered ADME of drugs have been observed in Covid-19 infection and vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, altered ADME of drugs have been observed in Covid-19 infection and vaccination. A clinical case study reported that an increased level of clozapine was observed in an individual with history of oral clozapine treatment over 10 years after receiving mRNA vaccine (Pfizer-BioNTech) for SARS-CoV-2 [ 143 ]. The individual showed symptoms of Covid-9 infection although tested negative repeatedly as well as multiple comorbidities associated with increased risk of neurologic toxicity of clozapine [ 143 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…chemokines and cytokines, and cellular recruitment [ 125 ]. The activated innate immune response generally decreases CYP enzyme activity, and these interactions extend to drug transporters and organs, impacting drug absorption, distribution, metabolism and excretion (ADME) [ 126 ]. Therefore, altered ADME is predicted after SARS-CoV-2 (COVID-19) vaccination [ 126 ].…”
Section: Covid-19 Vaccines: Cyp2c9 Downregulationmentioning
confidence: 99%
“…Spike glycoprotein of SARS-CoV-2 is one of the major targets of the host immune system. , Receptor-binding domain (RBD) is immunodominant and accounts for major neutralizing activity in the serum of convalescent COVID-19 patients. , However, spike glycoprotein and RBD both suffer from inherently low immunogenicity and poor pharmacokinetics . Appropriate adjuvant or delivery system is an alternative to enhancing the immune effectiveness of the antigens …”
Section: Introductionmentioning
confidence: 99%